2020
DOI: 10.1111/jgs.16399
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hemorrhage in Older Adults: Implications for Fall Risk Assessment and Prevention

Abstract: This editorial comments on the article by https://doi.org/10.1111/jgs.16400. and https://doi.org/10.1111/jgs.16338.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Comparative studies between the elderly versus younger age have indicated that women were predominant above the age of 65 years, 70 years, or with increasing age. 12,13 In the present study, ICH was the most common vascular diagnosis followed by SAH. ICH is a growing cause of mortality and morbidity worldwide, because of the increasing number of elderly people.…”
Section: Discussionmentioning
confidence: 52%
“…Comparative studies between the elderly versus younger age have indicated that women were predominant above the age of 65 years, 70 years, or with increasing age. 12,13 In the present study, ICH was the most common vascular diagnosis followed by SAH. ICH is a growing cause of mortality and morbidity worldwide, because of the increasing number of elderly people.…”
Section: Discussionmentioning
confidence: 52%
“…There has been recent debate about the suitability of CT scanning low-risk patients (35). The AHEAD study concluded that the decision to recommend CT scanning in guidance should take into account the potential benefits, harms and costs of CT scanning (18).…”
Section: Anticoagulants and Intracranial Hemorrhagementioning
confidence: 99%
“…Some risk factors for ICH in the general adult population include smoking, cerebral amyloid angiopathy, drug/alcohol use, and pre-existing comorbidities such as hypertension, diabetes mellitus (DM), heart disease and chronic kidney disease 11,12 . In addition, anticoagulation usage is strongly associated with higher mortality and disability rates 10,13 . Most, if not all of these risk factors are likely to be more prevalent in older patients and age itself is one of the greatest independent risk factors for spontaneous ICH 12,14 .…”
Section: Introductionmentioning
confidence: 99%